2019
DOI: 10.4314/ovj.v8i4.22
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocartilaginous embolic encephalopathy of the cerebellum and brainstem in a cat

Abstract: A 12-year old male castrated Siamese cat was evaluated for a one-day history of mild obtundation and decerebellate rigidity. Neurological examination findings were consistent with multifocal disease including lesions within the right cerebellum and right brainstem. Investigations included hematology, biochemistry, urinalysis, and urine culture. A definitive diagnosis was not achieved clinically and differential diagnoses included vascular disease, neoplasia, and infectious disease. About nine hours after admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In one of the cases of this study, FCE affected the cerebellum. This lesion distribution is not commonly observed in cases of FCE, with rare reports in veterinary literature [ 47 ]. In this case, it is suggested that the nucleus pulposus may have originated from the cervical segment of the vertebral column, and the material entered small arteries, and occluded the lumen of vertebral arteries retrogradely, similarly to previous descriptions [ 42 , 48 ].…”
Section: Discussionmentioning
confidence: 95%
“…In one of the cases of this study, FCE affected the cerebellum. This lesion distribution is not commonly observed in cases of FCE, with rare reports in veterinary literature [ 47 ]. In this case, it is suggested that the nucleus pulposus may have originated from the cervical segment of the vertebral column, and the material entered small arteries, and occluded the lumen of vertebral arteries retrogradely, similarly to previous descriptions [ 42 , 48 ].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, neutrophilic pleocytosis and neutrophilic infiltration of the spinal cord were interpreted as a reaction to neuroparenchymal necrosis. Accordingly, neutrophilic pleocytosis has been described in the CSF of cats with myelomalacia secondary to fibrocartilaginous embolism, 20 and mild neutrophilic infiltration of the spinal cord has been histologically described in a cat with haemorrhagic myelomalacia. 21 These findings were therefore consistent with an iatrogenic needle injury and potential injection.…”
Section: Discussionmentioning
confidence: 99%